Data Sampling Frequency Effects on Risk-Adjusted Cryptocurrency Portfolio Construction - El Kehal, Kamal; Ennagoura, Drissia; El Fahssi, Khalid; Bossoufi, Badre; El Far, Mohamed; Bennani, Mohamed Taj (Engineering, Technology & Applied Science Research, 2026)
The cryptocurrency market exhibits a high level of volatility, and the process of portfolio construction can be complex and highly lucrative. Issues related to portfolio construction in the cryptocurrency market are targeted in this paper through the assessment of the effect of sampling frequency on cryptocurrency portfolio optimization. A detailed analysis of the effect of three specific sampling frequencies (15 minutes, 1 hour, and 1 day) was undertaken, and the activities of eight top cryptocurrencies (ADA, BTC, DOGE, ETH, LTC, SOL, TRX, and XRP) were considered. Using price information sourced from the KuCoin exchange from 2023 to 2025, we are able to conduct a risk-adjusted optimization-based analysis to determine the optimal portfolio composition while utilizing the Sharpe Ratio measure to determine portfolio performance. The effect of sampling frequency on portfolio composition, as well as on the estimate of the risk/return profile and correlation measures, proved to be significant.